The role of time in the creation of a collective spiritual essence in a sailing school. Issue 1 (2nd January 2020) - Galeazzi, Gilberto
ABSTRACT: The paper concerns time and its role in the creation of a spiritual collective essence in the context of an Italian sailing school, the Centro Velico Caprera. The article focuses on how the implementation of a particular time frame contributes to the creation of the 'Spirit of Caprera', a set of disposition, characteristics and collective essence, by enhancing and constructing specific dynamics that appear to have a central role in the sailing school. The article aims to explain the relationship between time, school and spirit and to show how they interact with one another. The everyday routine of the school, and the significance that some moments gain, appear to be the ground on which the institution bases its life, sense of belonging and particularities.